Factors affecting the efficiency of a water splitting photocatalyst: a perspective - Gupta, Narendra M. (Renewable & Sustainable Energy Reviews, 2017)
To design an efficient photocatalyst (PC) for semiconductor (SC)-mediated, solar-driven water dissociation to generate hydrogen, a host of strategies has been adopted, including the fabrication of semiconductor composites, substitution of impurities for achieving extended absorbance, and coating with a metal to promote charge transfer. Despite these efforts, a photocatalyst exhibiting requisite efficiency has not been developed. This article reviews the factors governing the water splitting photoactivity of an SC material, and provides an account of our recent research on this subject. As per our investigations, the mode of adsorption of the water molecules on the semiconductor surface and their subsequent interaction with the charge carriers play a crucial role in the overall performance of a water splitting photocatalyst, rather than the much-discussed SC SC or SC -> metal charge transfer effects alone. The water to-SC binding is controlled by a combination of several physicochemical properties of a composite PC, such as the preparation-dependent grain morphology, doping affected grain nucleation, pore structure-dependent water adsorption/desorption kinetics, exposure of specific facets, and SC/SC or SC/metal interfacial characteristics. Our studies revealed strong particle size dependence and the facet-based sensitivity of modified metal sulfide and metal oxide photocatalysts. Additionally, the effect of lattice impurity on quantum efficiency of wide gap metal oxides, such as TiO2, In2TiO5, InVO4, FeNbO4, GaNbO4, GaFeO3, and LaInO3, is related to the lattice-defect-induced intra-bandgap energy levels rather than the doping-induced extension of visible region absorbance. Furthermore, the dispersed gold natoparticles served as distinct reaction sites over the surface of a TiO2 photocatalyst besides their contribution to the plasmonic effect. Our study revealed that under certain spectral overlap conditions, the inter-semiconductor charge transfer might cause quenching of the water splitting photoactivity Of a composite photocatalyst. We surmise that considering the aforementioned factors should assist in designing an efficient water splitting PC, eventually triggering technological advancements in this field.